Andhra Pradesh: looking beyond vision 2020 - Bandyopadhyay, D. (2001)
Where landlessness and exploitative informal tenancy relationships are the major causes of acute rural poverty and where the bureaucracy has a proven track-record of not reaching the lowest layers of the poor, without land reforms and empowerment of panchayats the best intentions of the Andhra Pradesh government will not give the desired results, leading to enormous investment in the rural sector yielding sub-optimal social returns. - Reproduced
Keywords: Poverty - India - Andhra Pradesh; Poverty